Examining the Treatment of Disabled Persons in the Kingdom of Saudi Arabia and an Analysis of Rights Violations - Alharbi, Sumiah (Curtin University, 2022)
This study reviews issues faced by disabled persons in Saudi Arabia and actions that could be taken to address the hindrances to their enjoyment of human rights in the country. It is based on a doctrinal examination of the laws and regulations relating to disabled persons in Saudi Arabia and a comparison with other countries to determine if the laws adequately protect the fundamental human rights of disabled persons.